APLIKASI BIOKOMPOS STIMULATOR Trichoderma spp. DAN BIOCHAR TEMPURUNG KELAPA UNTUK PERTUMBUHAN DAN HASIL JAGUNG (Zea mays L.) DI LAHAN KERING - Wawan Apzani; I Made Sudantha; M. Taufik Fauzi (Faculty of Agricultural Technology, University of Jember, 2015)
The objective of this research was to investigate the effect of applying biocompost stimulated by Trichoderma spp. and biochar from coconut shell on the growth and yield of maize (Zea mays L.) in the dryland of Akar-akar village, Sub-district of Bayan, North Lombok. A field experiment had been carried out from August to December 2014 by using Split Plot design and Randomized Completelly Block Design (RCBD) with two factors namely biocompost and biochar. The biocompost as sub plot was applied at the rate of 0, 5, 10, 15, 20, or 25 tonnes/ha; whereas the biochar as mai n plot was applied at the rate of 0 or 20 tonnes/ha. The treatments were replicated three times. The result showed that biocompost stimulated by Trichoderma spp. could significantly increase the growth and yield of maize. The application of biocompost at the rate of 15 tonnes/ha could increase the growth and yield of dry shelled maize till 6,2 tonnes/ha.Keywords: biocompost, biochar, growth, yield, maize